(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The study aims to assess the benefits of bank mergers from the point of view of bankers and researchers. As merger of banks has been taking place in India in regular intervals, extensive research is conducted in the study to analyse the benefits of merger. Primary and categorical data has been used for the study. A scheduled questionnaire is prepared for data collection. A total of 217 responses are processed for the study purpose. Six factors are extracted from exploratory factor analysis. It is found that bank merger has financial benefit and market benefit. The present study will help bankers to design a comprehensive merger strategy.